Enhancement of pedestrian network system in Johor Bahru City Centre [electronic resource] - Mohamed Omar Mohamed Mashri, 1976- (2008)
Thesis (Sarjana Sains (Rekabentuk Bandar)) - Universiti Teknologi Malaysia, 2008